Factors influencing attitude towards technology adoption among Permanent Food Production Park program participants of selected states in Peninsular Malaysia - Zulqarnain, . (2021)
The Malaysian government has been focusing on innovation, research and development through the integration of technology and agriculture. The Permanent Food Production Park (PFPP) programme was introduced by the government, aiming to increase food production, decrease foods import and to support the application of large scale of agriculture entrepreneurs. This study aimed to explore the factor influencing attitude towards technology adoption among PFPP programme participants in West Malaysia. The specific objectives of this study were: 1) To describe the socio-demographic and farm profile of PFPP participants; 2) to determine the attitude level towards technology adoption among PFPP farmers; 3) to determine the factors associated with farmers’ attitude towards technology adoption. The study adopted a cross-sectional study design and was conducted in four states in Malaysia namely; Negeri Sembilan, Selangor, Perak and Johor. The studied population included the PFPP programme participants with a sample size of 275 farmers selected using a simple random sampling technique. The data were collected using a well-structured questionnaire that was initially pilot tested and validated. To achieve the stated objectives, five (5) main constructs were considered as independent variables based on relevant theories and previous studies. These constructs included respondents’ socio-demographic characteristics, farm profile, perceived benefits of technology, perceived measures to improve technology adoption, and perceived role of agricultural officers. The obtained data were analyzed by applying descriptive analysis, independent T-tests, and multiple regression analysis using the Statistical Package for Social Sciences (SPSS, version 22). Most of the respondents in this study were males (93.5%), 45.5% were above 50 years old and 68.0% were Muslims. The majority of respondents were Malays (67.6%) followed by Chinese (29.1%), and less than 5% were Indians or belonging to other ethnicities. The majority (76.8%) of respondents had either primary or secondary education. In terms of farm profile, most respondents (96.7%) had farm size ranging from 1-30 hectares and 70.9% of them used TKPM land for their farming activities. A higher proportion of respondents (36.7%) earned less or equal to RM10,000 as gross income while 25.8% earned between RM10,001 - RM50,000. Based on the analysis of all items measuring farmers’ attitude level, 89.1% of the respondents had good attitude towards technology adoption. Further analysis showed that only 31.6% of the participants had high adoption level of technology in agricultural practices. Farmers with primary to standard six education had a significantly lower attitude score (B = -2.06; 95% CI -3.09, -1.04; P = 0.0001) compared to those with higher education. The farmers who owned and rented a land for farming purposes tended to have higher attitude score (B = 2.41; 95% CI -0.03, 4.86; P = 0.05) compared to those belonging to the TKM and surrogate land owners. Furthermore, farmers with the minimum net income (less or equal RM 10,000) had a significantly lower attitude score (B = -1.89; 95% CI -0.34, -3.44; P = 0.017) compared to those earning more than RM 100,000. Each unit increase in farmers’ scores for items measuring the impact of technology was associated with an increased attitude score towards technology adoption (B = 0.11; 95% CI 0.14, 0.08; P = 0.0001). Similarly, a unit increase in farmers’ scores for measures perceived to motivate farmers was associated with an increased attitude score towards technology adoption (B = 0.19; 95% CI 0.19, 0.07; P = 0.0001). These findings indicated that these factors could be used by appropriate authorities when developing strategies to improve technology adoption amongst participants of PFPP.